Evidence from Unpaywall on Open Access Adoption among Indian Researchers - Zia, Sana (Journal of Data Science, Informetrics, and Citation Studies)
This study examines the patterns, trends and adoption of Open Access (OA) publishing among Indian researchers, with a focus on selected Indian Institute of Technology (IIT). Using publication data from Scopus and OA metadata from Unpaywall for the period 2020-2024, the analysis explores institution-wise outputs, OA evidence types, hosting platforms, licensing practices, OA versions and publication genres. Results indicate that Closed Access publications dominate across all institutions, although both Gold and Green OA show consistent growth. Publisher platforms emerge as the primary hosts, while Creative Commons (CC) licenses remain sparsely adopted. Most OA publications correspond to the final published version, with journal articles comprising over 99% of the OA corpus. Overall, IITs exhibit higher OA participation compared to the national average, yet fall short of global best practices in repository use, licensing transparency and preprint adoption. Strengthening institutional mandates and implementing supportive policies are crucial to enhance the visibility, accessibility and international impact of Indian research.
Keywords: India; Indian Institute of Technology; Open Access (OA); Researchers; Unpaywall.